1999
DOI: 10.1107/s0909049599001363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solvation on the structure of the transition metal complexes in solutions

Abstract: CdK EXAFS, ZnK and CuK EXAFS and XANES spectra were measured for solutions of cadmium, zinc and copper dialkyldithiocarbamates in organic solvents with varying donating abilities: benzene, pyridine, tributylphosphine and for some model compounds. The parameters of the local surroundings of the Cd, Zn and Cu atoms for complex forms in solutions were determined using EXAFS spectroscopy. Spatial structure models of the complex forms in a metal chelate -nonaqueous solvent system are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…EXAFS spectra and Fourier Transforms of typical octahedral Fe(II)-triazole and tetrazole complexes in both Low Spin (LS) and High Spin (HS) states has been already published (Erenburg, 1999), including FEFF multiple scattering calculation for the triazole rings (Yokoyama, 1998) and even for the Fe-Fe-Fe alignment (Michalowicz, 1995(Michalowicz, , 1997(Michalowicz, , 1999, (Garcia, 1997), (Van Koningsbruggen, 2000). They concluded that the multiple scattering peak at 7 Å is a suitable signature of the Fe-Fe-Fe alignment in the polymeric series.…”
Section: Resultsmentioning
confidence: 99%
“…EXAFS spectra and Fourier Transforms of typical octahedral Fe(II)-triazole and tetrazole complexes in both Low Spin (LS) and High Spin (HS) states has been already published (Erenburg, 1999), including FEFF multiple scattering calculation for the triazole rings (Yokoyama, 1998) and even for the Fe-Fe-Fe alignment (Michalowicz, 1995(Michalowicz, , 1997(Michalowicz, , 1999, (Garcia, 1997), (Van Koningsbruggen, 2000). They concluded that the multiple scattering peak at 7 Å is a suitable signature of the Fe-Fe-Fe alignment in the polymeric series.…”
Section: Resultsmentioning
confidence: 99%